Structural microvibration monitoring and simulation analysis of the proton service building based on the construction process. (October 2020) - Yu, Penghao; Zhang, Yingying; Gao, Zhenyu; Song, Wei; Zhao, Yushuai
Abstract: For specific high-precision instruments, such as proton therapy equipment, microvibrations of the surrounding environment directly affect the equipment's use effect. In this paper, based on structural microvibration monitoring in the construction process, a foundation-structure finite element modeling method was verified under heavy vehicle conditions. The study revealed the microvibration response of different structural forms under different heavy vehicle conditions. The effects of different heavy vehicle mass, distance, speed, and structural stiffness levels on structural microvibrations were studied. The results showed that the primary response of structural microvibration under heavy vehicle conditions was vertical vibration, and the effects of the heavy vehicle distance and mass on the structural microvibrations were notable. Due to the existence of foundation soil, the structural microvibration response was not sensitive to the change in structural stiffness. Finally, through regression analysis of the numerical results, a structural microvibration evaluation equation was obtained for the studied building under heavy vehicle conditions. The equation suitably fits the monitoring and numerical results, which provides a basis for microvibration evaluation of similar structures.